2022
DOI: 10.3389/fonc.2022.918296
|View full text |Cite
|
Sign up to set email alerts
|

Setup error assessment based on “Sphere-Mask” Optical Positioning System: Results from a multicenter study

Abstract: BackgroundThe setup accuracy plays an extremely important role in the local control of tumors. The purpose of this study is to verify the feasibility of "Sphere-Mask" Optical Positioning System (S-M_OPS) for fast and accurate setup.MethodsFrom 2016 to 2021, we used S-M_OPS to supervise 15441 fractions in 1981patients (with the cancer in intracalvarium, nasopharynx, esophagus, lung, liver, abdomen or cervix) undergoing intensity-modulated radiation therapy (IMRT), and recorded the data such as registration time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…S-M_OPS adopts point registration, which is a type of rigid registration ( 22 ). After 7 years of clinical trials [2016–2022], S-M_OPS has been demonstrated to be accurate and reliable ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S-M_OPS adopts point registration, which is a type of rigid registration ( 22 ). After 7 years of clinical trials [2016–2022], S-M_OPS has been demonstrated to be accurate and reliable ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study showed that Sphere-Mask Optical Positioning System (S-M_OPS) was not affected by imaging quality and provided comparable localization accuracy to CBCT. Hence, it could supervise CBCT-guided registration accuracy ( 33 ).…”
Section: Introductionmentioning
confidence: 99%